Geschichtsaufarbeitung und Vergangenheitsbewältigung in Rumänien nach 1989 - Brigitte Albu (Historia.scribere)
The purpose of this paper is to analyse the Romanian post-communist era with regard to the Romanians’ treatment of their past. How did the government deal with its communist past and has it officially been condemned? Was it possible for the people to move on after Ceaușescu’s death? The main source for the analysis is a Romanian document published in 2006 by a presidential commission under leadership ofVladimir Tismăneanu : the Tismăneanu-report.